2021
DOI: 10.1016/j.ajur.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Blood and urine biomarkers in prostate cancer: Are we ready for reflex testing in men with an elevated prostate-specific antigen?

Abstract: Objective There is no consensus on the role of biomarkers in determining the utility of prostate biopsy in men with elevated prostate-specific antigen (PSA). There are numerous biomarkers such as prostate health index, 4Kscore, prostate cancer antigen 3, ExoDX, SelectMDx, and Mi-Prostate Score that may be useful in this decision-making process. However, it is unclear whether any of these tests are accurate and cost-effective enough to warrant being a widespread reflex test following an elevated PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 86 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…This is consistent with studies that have shown that serum PSA levels do not distinguish between low-grade and clinically significant PCa. , Several other diagnostic biomarkers have been developed to improve the prediction of clinically significant PCa. Some of these include PHI, 4Kscore, and the ExoDx IntelliScore. , Recent reviews of these methods concluded that while all these tests have clinical utility, they do not add substantially in diagnostic value and are relatively costly to perform. , For example, the AUCs for each of these tests are 0.652, 0.67, and 0.73, respectively. In contrast, the newly developed %α23PSA assay, if used after PSA, would enable clinical laboratories to reduce unnecessary biopsies by 85% if implemented in the diagnostic pathway of localized PCa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with studies that have shown that serum PSA levels do not distinguish between low-grade and clinically significant PCa. , Several other diagnostic biomarkers have been developed to improve the prediction of clinically significant PCa. Some of these include PHI, 4Kscore, and the ExoDx IntelliScore. , Recent reviews of these methods concluded that while all these tests have clinical utility, they do not add substantially in diagnostic value and are relatively costly to perform. , For example, the AUCs for each of these tests are 0.652, 0.67, and 0.73, respectively. In contrast, the newly developed %α23PSA assay, if used after PSA, would enable clinical laboratories to reduce unnecessary biopsies by 85% if implemented in the diagnostic pathway of localized PCa.…”
Section: Resultsmentioning
confidence: 99%
“…14,50−52 Recent reviews of these methods concluded that while all these tests have clinical utility, they do not add substantially in diagnostic value and are relatively costly to perform. 17,50 For example, the AUCs for each of these tests are 0.652, 31 0.67, 32 and 0.73, 51 respectively. In contrast, the newly developed %α23PSA assay, if used after PSA, would enable clinical laboratories to reduce unnecessary biopsies by 85% if implemented in the diagnostic pathway of localized PCa.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many biomarkers (e.g., 4 K score, prostate health index, Progensa PCA3 38–40 ) can be used as a RAT in this model. In the base case, we used the characteristics of SelectMDx, a urine‐based molecular biomarker, 41 for the RAT strategy as an illustrative example to demonstrate the functionality of our model and to make our findings comparable to previous economic evaluation studies 19,20,28 .…”
Section: Methodsmentioning
confidence: 99%
“…SelectMDx is a novel urine-based risk score, which combines urinary biomarkers homeobox C6 (HOXC6) and distal-less homeobox 1 (DLX1) with traditional clinical factors such as age, PSA, digital rectal examination (DRE), prostate volume, and family history of PCa to assess the probability of risk of suffering clinical significant PCa (Gleason score � 7 or Grade group � 2) [17][18][19]. This risk score could reach a sensitivity of 96% and a specificity of 53% in the validation cohort [20].…”
Section: Introductionmentioning
confidence: 99%